A Comparative Analysis of Hotel Staff Opinions on the Positive Effects of Tourists by Demographic Variables: The Cases of Antalya and Eskişehir Provinces - Oktay, Emir (Turizam, 2018)
The factor of employee quality is crucial in tourism because it is a sector focused primarily on serving individuals. The fact that hotel establishments are expected to provide 24/7 uninterrupted service makes it more important that the customers and employees are in constant communication and the employees are qualifed. Tourists always wish to have happy momentsthroughout their travel and hope to return home with cherishable memories of the trip. For this reason, hotel staﬀ opinions about the positive eﬀects of tourists will contribute both to the tourism sector and to serving tourists better. According to the results of the study, while no signifcant relationship was found between the demographic characteristics of the employees andthe perceived positive eﬀects of tourists staying in Antalya hotels, certain diﬀerences emerged concerning some staﬀ demographics in Eskişehir.